An exponential continuous time GARCH process - Stephan Haug; Claudia Czado (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2006)
In this paper we introduce an exponential continuous time GARCH(p, q) process. It is defined in such a way that it is a continuous time extension of the discrete time EGARCH(p, q) process. We investigate stationarity and moment properties of the new model. An instantaneous leverage effect can be shown for the exponential continuous time GARCH(p, p) model.
urn:nbn:de:bvb:19-epub-1848-4
Keywords: 519; exponential continuous time GARCH process; EGARCH; Lévy process; stationarity; stochastic volatility